The contribution of forest foods to sustainable diets: Background paper for the International Conference on Forests for Food Security and Nutrition, FAO, Rome, 13-15 May 2013 - Vinceti, B.; Ickowitz, A.; Powell, B.; Kehlenbeck, K.; Termote, Céline; Cogill, Bruce; Hunter, D. (Food and Agriculture Organization of the United Nations, 2013)
With the growing demands from a population expected to reach 9 billion people by 2050, it is unclear how our current global food system will meet future food needs. Ensuring that all people have access to adequate and nutritious food produced in an environmentally and socio-culturally sustainable manner is one of the greatest challenges of our time. Forest foods represent an affordable source of food, especially for those with limited livelihood options, supplying micronutrients, fibres and other key food components most commonly lacking from diets.This background paper examines the largely untapped potential for forest foods to contribute to food security and better nutrition, as elements of sustainable diets. Full realization of the contribution of forest and tree foods to sustainable diets faces a number of constraints. The paper presents some key issues; among these are knowledge gaps, issues related to tenure and access, aspects of sustainability of extraction, and rapidly evolving social and cultural contexts, which have a significant impact on diets. Research is needed on all these topics.Finally, the paper identifies research gaps and makes recommendations to enhance the contribution of forest foods to sustainable diets.